Automatic Control System of Railway Traffic Signal on Account of Distributed Appraisal Algorithm - Xiongsheng Wu, Hanqing Tao, Zhengyi Wei (Forest Chemicals Review, 1970)
In the abstract, the computer is a rapidly developing Web tool that has profoundly changed all walks of life. The railroad transportation industry is no exception. Computer tools have came into service in the dodominating of railroad traffic. The curb of railroad traffic semaphore is a part curbled and scheduled by computer. Computer through its own technical advantages, reasonable curb and management of railroad transport. The semaphore curb platform ensures the daily affairs of railroad traffic efficiently, which is of great significance to the dodominating of intelligent railroad traffic. Now many scholars are discussing how to use semaphore curb platform to improve the operation capacity of railroad semaphore, so as to improve the level of economic benefits of railroad traffic. This text studies the railroad traffic semaphore automatic curb platform on account of distributed appraisal algorithm, which improves the key technology level of railroad traffic semaphore automatic curb. The data prove that the research of railroad traffic semaphore automatic curb platform on account of distributed appraisal algorithm has accurate and efficient performance in railroad traffic semaphore automatic curb.